The effect of menstrual cycle phase on exercise capacity measured by treadmill exercise test - Mehmet Yazıcı; Sadan Yazar (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to explore the impact of the menstrual phases on exercise capacity parameters measured by a treadmill exercise test in sedentary premenaupausal women. Exercise capacity expressed in terms of metabolic equivalents (MET) and exercise duration was measured by performing treadmill exercise tests in 30 women (mean age: 29 ± 5.8 years) with regular menstrual cycles at two points during their menstrual cycles: the late-follicular (LF) phase and the mid-luteal (ML) phase. The exercise duration was significantly higher (P lt; 0.05), and the exercise capacity (in MET) tended to be higher (P = 0.075) in the ML phase than in the LF phase. These results suggested that the menstrual phases in sedentary women can have an influence on exercise capacity. These changes may be attributed to the relative changes in the female steroid hormones between the LF and the ML phases.